Oxford handbook of clinical pharmacy - Wiffen, Phil; Mitchell, Marc; Snelling, Melanie; Stoner, Nicola
Complementing the guidelines in the British National Formulary, this third edition remains the indispensable guide to clinical pharmacy providing all the information needed for practising and student pharmacists.